Overcoming pathological gambling : therapist guide - Ladouceur, Robert (Treatments that work., 2007)
This Therapist Guide provides clinicians with session-by-session instructions for implementing an effective, CBT-based treatment for pathological gambling. The treatment outlined helps clients to not only overcome their problem, but also to deal with the many consequences of their excessive gambling including financial problems and interpersonal conflicts.